Evidence for the presence of heat-stable protein (HPr) and ATP-dependent HPr kinase in heterofermentative lactobacilli lacking phosphoenolpyruvate:glycose phosphotransferase activity. - Reizer, J (1988)
An analysis of the biochemical basis for the lack of phosphoenolpyruvate:glycose phosphotransferase activity in heterofermentative lactobacilli was carried out. Extracts of Lactobacillus brevis and Lactobacillus buchneri failed to reconstitute phosphotransferase activity of extracts of Staphylococcus aureus mutants impaired in the phosphotransferase system due to the absence of enzyme I, enzyme IILac, or enzyme IIILac activity, suggesting that these lactobacilli lack those phosphotransferase system components. In contrast, complementation tests with an extract of a S. aureus mutant deficient in heat-stable protein (HPr) indicated the presence of HPr activity in heterofermentative lactobacilli. The HPr of L. brevis was purified and shown to have properties similar to those of a typical HPr. In addition, L. brevis possesses an ATP-dependent protein kinase that phosphorylates a serine residue of the endogenous HPr as well as other HPrs of Gram-positive origin. The kinase activity is markedly stimulated by phosphorylated compounds related to sugar metabolism and is negatively modulated by orthophosphate, pyrophosphate, or arsenate and by a low molecular weight endogenous factor. In keeping with the idea of a regulatory role for the phosphorylation of HPr in lactobacilli, a HPr[Ser(P)] phosphatase activity in L. brevis was also demonstrated. On the basis of the finding of HPr and a system for its reversible covalent modification in an organism devoid of a functional phosphotransferase system we propose that, in lactobacilli, HPr has a role in the regulation of pathways other than the phosphotransferase system.